Development of a scalable tabletop display using projection-based light field technology - Hamong Shim (Taylor & Francis Group, 2021)
We present a light-field display optical system design, state-of-the-art hardware technology, and computational software that are readily scalable (due to their modular structure) and provide naturally immersive and volumetric display systems. We explain the integration of 72 microprojectors into the tabletop display system. In addition, we used 6 workstations for all images and 18 high-performance graphics processing units. Sophisticated image generation through author tooling and the pixel re-arrangement algorithm in the Unity engine enabled us to produce complete three-dimensional images from the radiant rays of two-dimensional pixels using diffuser screens and microlens arrays.